The blossoming summer - Johnson, Anna Rose (Holiday House, 2025)
When thirteen-year-old Rosemary is evacuated from WWII London to her grandmother's home in America, she uncovers a hidden family truth -- that they are Anishinaabe -- leading her to embrace her heritage, forge new bonds, and find beauty in unexpected places.